PENGARUH PROFESIONALISME KERJA PEGAWAI TERHADAP TINGKAT KEPUASAN PELANGGAN PADA KANTOR PT. TASPEN CABANG MANADOâ€. - TAMRIN, AGUNG SAPUTRA; Rumapea, Patar; Mambo, Rully (JURNAL ADMINISTRASI PUBLIK, 2017)
Abstract:this research aims to know the influence of professionalism of employeesworking toward customersatisfaction rate on PT. TASPEN Manado Branch. This research using quantitative methods. Therespondents in this study amounted to 36 people atthe customers Office PT TASPEN Manado Branch.Data collection instrumentsand techniques used are questionnaire and assisted withinterviews andobservation. Analytical techniques used for hypothesis testing is the analysis of thecorrelation of product moment and a simple linear regression analysis assistedby data processing computer program SPSS version 13.0. The results of data analysis in this researchindicate: (1) there is a positive relationship between the variable profesioalisme of work employees andcustomer satisfaction with r = 0.773 count greater than r table with df (N-2 = 36-2 = 34) on thesignificance level 0.01 = 0.2785. (2) price determination coefficient (r ^ 2) of 0.597 gives a clue thatvariable professionalism of work employees (X) contributing positively to the development of 59.7%customer satisfaction variable (Y) PT TASPEN Branch Office in Manado, whereas the rest of 40.3%influenced by another factor that is outside of this research study. (3) the degree of correlation anddetermination of variable employee against the working professionalism of customer satisfaction this isreal and significant degrees of 0.01 or at level 99% confidence, as indicated on the test of significance (ttest)which gained value t calculate = of 7.094 that have a difference greater than the value of the t tableon the extent the significance of 0.01.Keywords: Professionalism Of Work, Employees, Customer SatisfactionPENDAHULUANSatu hal yang menjadi perhatianadalah sifat eksklusifitas dari PT TASPEN itusendiri, dimana ‘monopoli’ pemberian jasajaminan sosial kepada PNS telahmembebaskan PT TASPEN dari masalahpersaingan usaha. Seperti diketahui bahwapersaingan usaha bagaimanapun bentuknyatelah menjadi salah satu indikator dalampeningkatan kualitas pelayanan khsususnya disektor swasta.Ketiadaan persaingan usaha yang relevanhingga luas dan terjaganya pangsa pasar dariPT. TASPEN itu sendiri menjadi menarikuntuk kemudian dilihat bagaimana prosespemberian pelayanan kepada pelanggandalam konteks pelaksanaan good governanceitu dilaksanan dengan berorientasi padakepuasan pelanggan.Berdasarkan latar belakang masalahdiatas, penulis tertarik untuk meneliti tentang“Pengaruh Profesi